Parental mediation in a mediatised world: Digital media as a challenge for parents' role in education (Pedagogical Horizons, 2025)
This article provides insight into the challenges faced by parents in supporting children and young people as they develop in a world heavily influenced by media, and in preparing them for future tasks, including in the digital sphere. Digital media play an increasingly important role in the development of children and young people, as they are an integral part of everyday family life from birth and accompany them as they grow up. This study examines the different ways in which media are used in families and their influence on the media behaviour of children and young people. This raises the question of what strategies for parental media education are recommended in the literature in order to adequately support children and young people in the development process of a mediatised world.
Keywords: mediatisation; media education; media socialisation